Antiinflammatory and antiproliferative activity of naphthoxazole, fused hetero-benzoxazole and bridged benzobicyclic photoproducts - Šagud, Ivana (Array, 2019)
Biological activity of naphthoxazoles, fused hetero-benzoxazoles and benzobicyclo[3.2.1]-derivatives was investigated in proliferation and inflammation based assays. The tested compounds were prepared by photocylization or photocycloaddition reactions. Effect of compounds on proliferation of several cancer cell lines was determined by measuring cell metabolic activity through time. Lipopolysaccharide (LPS) stimulation of peripheral blood mononuclear cells (PBMC) was used to investigate antiinflammatory properties of the compounds. Several naphthoxazoles and fused hetero-benzoxazoles inhibited TNFα protein expression in LPS stimulated PBMC, indicating possible antiinflammatory role which would be interesting to further investigate. Physico-chemical properties of tested compounds have been also studied using chromatographic lipophilicity measure, chrom logD and logP was calculated as the importance of physico-chemical properties of compounds at early stage of discovery of new drugs is well established. The similarities in structure and activity of some representative compounds affirm the need to further address their antiinflammatory properties.